Laser exfoliation of 2D black phosphorus nanosheets and their application as a field emitter - Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2016)
Highly crystalline two dimensional (2D) few layered black phosphorus (BP) nanosheets have been synthesized via a one step facile laser irradiation technique under optimized experimental conditions. The field emission investigations on the few layered black phosphorus nanosheets were carried out at the base pressure 1 x 10(-8) mbar. The morphological, elemental, optical, and structural analysis of the as-synthesized black phosphorus sample was carried out using SEM, AFM, EDAX, TEM, and Raman spectroscopy. The turn-on values of the BP nanosheets emitter were found to be significantly lower than that of earlier reports of BP nanosheets, graphene, and carbon nanotubes based field emitters due to the high field enhancement factor (beta) similar to 2986 associated with atomically thin/sharp edges of the BP nanosheets emitter. The emission current versus time plot depicts the good emission current stability with a pre-set value of 1 mu A for similar to 5 h duration. Our facile synthesis approach and the robust field emitter nature of the BP nanosheets makes them a potential candidate for a practical electron source in vacuum micro/nanoelectronic devices.

Low frequency noise and photo-enhanced field emission from ultrathin PbBi2Se4 nanosheets - Suryawanshi, Sachin R.; Guin, Satya N.; Chatterjee, Arindom; Kashid, Vikas; More, Mahendra A.; Late, Dattatray J.; Biswas, Kanishka (Journal of Materials Chemistry C, 2016)
Atomically thin two-dimensional layered materials have gained wide interest owing to their novel properties and potential for applications in nanoelectronic and optoelectronic devices. Here, we present the spectral analysis and photo-enhanced field emission studies of a layered intergrowth PbBi2Se4 nanosheet emitter, performed at the base pressure of similar to 1 x 10(-8) mbar. The emitter shows a turn-on field value of similar to 4.80 V mu m(-1), corresponding to an emission current density of similar to 1 mu A cm(-2). Interestingly, when the cathode was illuminated with visible light, it exhibited a lower turn-on field of B3.90 V mm(-1), and a maximum emission current density of similar to 893 mu A cm(-2) has been drawn at an applied electric field of similar to 8.40 V mu m(-1). Furthermore, the photo-enhanced emission current showed reproducible, step-like switching behavior in synchronous with ON-OFF switching of the illumination source. The emission current-time plots reveal excellent stability over a duration of similar to 6 h. Low-frequency noise is a significant limitation for the performance of nanoscale electronic devices. The spectral analysis performed on a Fast Fourier Transform (FFT) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha similar to 0.99. The low frequency noise, photo-enhanced field emission, and reproducible switching behavior characterized with very fast rise and fall times propose the layered PbBi2Se4 nanosheet emitter as a new promising candidate for novel vacuum nano-optoelectronic devices.